2017
DOI: 10.3892/etm.2017.4921
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions in depressed children with low serum levels of BDNF

Abstract: The purpose of this study was to investigate the correlation between brain-derived neurotrophic factor (BDNF) in serum and depression in children, and explore the effects of different nursing protocols on patients with low levels of BDNF. We recruited 128 children with depression and 50 healthy subjects. Compared with healthy controls, the mRNA and protein levels of BDNF in serum were lower in children with depression (p<0.01). We selected 60 depressed children with low BDNF and randomly divided them in two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…This suggests that reduced BDNF may be associated with the diagnosis of depressive disorder. Sun et al observed lower BDNF levels in patients with depressive disorder [64]. In this study, the group receiving comprehensive treatment showed higher serum BDNF levels than the group receiving routine treatment.…”
Section: The Cytokines In Neuroinflammationsupporting
confidence: 50%
See 1 more Smart Citation
“…This suggests that reduced BDNF may be associated with the diagnosis of depressive disorder. Sun et al observed lower BDNF levels in patients with depressive disorder [64]. In this study, the group receiving comprehensive treatment showed higher serum BDNF levels than the group receiving routine treatment.…”
Section: The Cytokines In Neuroinflammationsupporting
confidence: 50%
“…The results of these changes in BDNF were relatively consistent in adults with MDD. However, in children and adolescents, the results were inconsistent [50][51][52]64].…”
Section: The Cytokines In Neuroinflammationmentioning
confidence: 98%
“…22 This scale has been used in some adolescent studies. 2325 A Chinese version of the scale suitable for teenagers was used in this study. 26…”
Section: Methodsmentioning
confidence: 99%
“…The results of these changes in BDNF levels were relatively consistent in adults with MDD. However, in children and adolescents, the results were inconsistent [ 55 , 56 , 57 , 69 ]. Table 2 shows a summary of the previous studies of BDNF in pediatric depressive disorder.…”
Section: Neuroimmune System and Pediatric Depressive Disordermentioning
confidence: 99%
“…This suggests that reduced BDNF levels may be associated with the diagnosis of depressive disorder. Sun et al observed lower BDNF levels in patients with depressive disorder [ 69 ]. In this study, the group receiving comprehensive treatment showed higher serum BDNF levels than the group receiving routine treatment.…”
Section: Neuroimmune System and Pediatric Depressive Disordermentioning
confidence: 99%